Visualization of carboxylesterase 2 with a near-infrared two-photon fluorescent probe and potential evaluation of its anticancer drug effects in an orthotopic colon carcinoma mice model. Issue 32 (18th March 2020) - Wang, Yan; Yu, Feifei; Luo, Xianzhu; Li, Mingshun; Zhao, Linlu; Yu, Fabiao
Abstract : We have established a near-infrared two-photon fluorescent probe for the detection of CE2 with high selectivity and sensitivity. Abstract : We establish a near-infrared two-photon fluorescent probe for the detection of CE2 with high selectivity and sensitivity. This probe exhibits low cytotoxicity and superior tissue penetration ability for evaluating the real-time activity of CE2 in living cells, in cancer tissues, and in a colon carcinoma mice model.